Mass-spectrometric fragmentation of sodium 2-(4-methyl-5-(thiophene-2-yl)-4H-1,2,4-triazole-3-ylthio)acetate - Salionov, V. A.; Varynskyi, B. A.; Parchenko, V. V.; Саліонов, Володимир Олександрович; Варинський, Борис Олександрович; Парченко, Володимир Володимирович; Салионов, В. А.; Варинский, Б. А.; Парченко, В. В. (Запорізький державний медичний університет, 2015)
The study of physical and chemical characteristics and establishing patterns of mass spectrometric fragmentation are the actual tasks of modern pharmaceutical science, have both scientific interest and practical importance. Aim. The purpose of our experiment was to confirm the identity and study patterns of mass spectrometric decomposition for sodium 2-(4-methyl-5-(thiophene-2-yl) -4H-1,2,4-triazoles-3-ilthio) acetate. Methods and results. The study was carried out on the apparatus LC MS / MS: LTQ Orbitrap. After completing MS scan, it has been established that the maximum peak in the chromatogram corresponds protonated ion 2-(4-methyl-5-(thiophene-2-yl)-4H-1,2,4-triazoles-3-ylthio)acetic acid m/z 256.0208, and empirical formula test compound - C9H9N3O2S2. MS/MS MH+ analysis showed that protonated molecule of the 2-(4-methyl-5-(thiophene-2-yl)-4H-1,2,4-3-triazole-3-ylthio)acetic acid under voltage in contact with molecules of helium in the collision cell was disintegrated from m/z 256.0208 into some fragments. The first time the mass spectrometric investigation sodium 2-(4-methyl-5-(thiophene-2-yl)-4H-1,2,4-triazoles-3-ylthio) acetate has been undertaken. Conclusions. It has been established that the fragmentation of the molecule initially occurs with the dissociation of water molecule from carboxyl group. Under the influence of gas the next to come off may be a carboxyl group. In course of further dissociation the bond between the sulfur atom and acetic residue is destroyed or disruption of a covalent bond between sulfur and carbon of 1,2,4-triazole occurs. Вивчення фізико-хімічних характеристик, а також встановлення закономірностей мас-спектрометричного розпаду є актуальними завданнями сучасної фармацевтичної науки, мають як науковий інтерес, так і практичну значущість. Мета експерименту – підтвердження індивідуальності та дослідження мас-спектрометричного розпаду для молекули натрій 2-(4-метил-5-(тіофен-2-іл)-4Н-1,2,4-тріазол-3-ілтіо)ацетату. Дослідження виконали на приладі LC MS/MS: LTQ Orbitrap. Після виконання МС сканування встановили, що максимальний пік на хроматограмі відповідає іону з m/z 256,0208, а емпірична формула досліджуваної сполуки – C9H9N3O2S2. MS/MS аналіз 2-(4-метил-5-(тіофен-2-іл)-4Н-1,2,4-тріазол-3-ілтіо)ацетатної кислоти (MH+ з m/z 256,0208) показав, що під дією напруги при зіткненні з молекулами гелію в комірці зіткнень відбувається розпад молекули на деякі фрагменти. Встановили, що руйнування молекули спочатку здійснюється з відривом молекули води від карбоксильної групи. Під впливом зіткнення з газом наступною може відриватися карбоксильна група. При наступному розпаді руйнується зв’язок між атомом сульфуру та оцтовим залишком або ж відбувається розрив ковалентного зв’язку між сульфуром і вуглецем 1,2,4-тріазолу. Изучение физико-химических характеристик, а также установление закономерностей масс-спектрометрического распада являются актуальными задачами современной фармацевтической науки, имеют как научный интерес, так и практическую значимость. Целью нашего эксперимента было подтверждение индивидуальности и исследование масс-спектрометрического распада для молекулы натрий 2-(4-метил-5-(тиофен-2-ил)-4Н-1,2,4-триазол-3-илтио)ацетата. Исследование проведено на приборе LC MS/MS: LTQ Orbitrap. После выполнения МС сканирования установлено, что максимальный пик на хроматограмме соответствует иону с m/z 256,0208, а эмпирическая формула исследуемого соединения – C9H9N3O2S2. MS/MS анализ 2-(4-метил-5-(тиофен-2-ил)-4Н-1,2,4-триазол-3-илтио)ацетатной кислоты (MH+ с m/z 256,0208) показал, что под действием напряжения при столкновении с молекулами гелия в ячейке столкновений проходит распад молекулы на некоторые фрагменты. Установлено, что разрушение молекулы сначала проходит с отрывом молекулы воды от карбоксильной группы. Под влиянием столкновения с газом следующей может отрываться карбоксильная группа. При дальнейшем распаде разрушается связь между атомом серы и уксусным остатком или же происходит разрыв ковалентной связи между серой и углеродом 1,2,4-триазола.
Мас-спектрометричний розпад молекули натрій 2-(4-метил-5-(тіофен-2-іл)-4Н-1,2,4-тріазол-3-ілтіо)ацетату
Масc-спектрометрический распад молекулы натрий 2-(4-метил-5-(тиофен-2-ил)-4Н-1,2,4-триазол-3-илтио)ацетата
Keywords: 1,2,4-triazoles; Mass Spectrometry; High Performance Liquid Chromatography; Ionization In Electrospray; 1,2,4-тріазол; мас-спектрометрія; високоефективна рідинна хроматографія; іонізація в електроспреї; 1,2,4-триазол; масс-спектрометрия; высокоэффективная жидкостная хроматография; ионизация в электроспрее